Draft genome sequences of Campylobacter fetus subsp. venerealis bv. venerealis strain B6 and bv. intermedius strain 642-21 - Barrero, R.; Moolhuijzen, Paula; Indjein, L.; Venus, B.; Keeble-Gagnère, G.; Power, J.; Bellgard, M.; Lew-Tabor, A. (American Society for Microbiology, 2014)
Campylobacter fetus subsp. venerealis is an important venereal pathogen. We sequenced the genomes of Campylobacter fetus subsp. venerealis bv. venerealis strain B6 and bv. intermedius strain 642-21. The genetic variability of these Australian strains will facilitate the study of mechanisms of geographical adaptation of these pathogens that impact livestock.